DECOLONIZING ANTHROPOLOGY: REVISITING INDIGENOUS KNOWLEDGE SYSTEMS IN THE CONTEXT OF GLOBALIZATION - Dr. Faris Al-Hussein (Modern American Journals, 2025)
Decolonization in anthropology involves challenging traditional academic practices and narratives that have often marginalized indigenous knowledge systems. This paper explores the process of decolonizing anthropology by revisiting indigenous ways of knowing and understanding the world, particularly in the context of globalization. Historically, anthropology has been criticized for its Eurocentric perspectives and its role in the exploitation and misrepresentation of indigenous cultures. However, with the rise of global interconnectedness, there is an increasing need to acknowledge and integrate indigenous knowledge systems into modern academic discourse. This research examines the role of anthropology in perpetuating colonial legacies and explores how indigenous epistemologies can contribute to contemporary global challenges, such as climate change, social justice, and cultural preservation. The paper also highlights the importance of indigenous self-determination in the redefinition of knowledge production and its implications for global anthropology.
Keywords: Decolonization, Anthropology, Indigenous Knowledge, Globalization, Epistemology, Cultural Preservation, Social Justice, Climate Change, Knowledge Systems, Indigenous Self-Determination.